Research on Electric Spot Trading of Electric Vehicles Based on Block Chain - ZHANG Zhening; ZHANG Xinyu; GONG Gangjun (Kongzhi Yu Xinxi Jishu)
Electric vehicle charging transaction is highly random, and when electric vehicles are connected to the grid in large scale, load volume of the distribution network will be affected to some extent.Therefore, efficient negotiation, safety and transparency have gradually become the inevitable development trend of the new charging transaction mechanism. This paper initially analyzed the multi-party negotiation demand of electric vehicles charging transaction, and a scene model of electric vehicles accessing ubiquitous power internet of things was proposed. Based on the trade demand and security demand, block chain technology was adopted to construct the real-time trade and regulatory node model. Secondly, combined with the security risks in real-time transaction, this paper established an electric vehicle charging transaction mechanism matching the actual block generation. Finally,by designing intelligent contract, the optimization process of trading scheme was validated by a genetic algorithm.The simulation results show that through the efficient operation of the smart contract of block chain, the formulation of the optimal trading scheme to meet the objectives of multiple participants is achieved, which can provide a reference for improving the safety, reliability and efficient coordination of the electric vehicle charging market.